Freedom crossing - Clark, Margaret Goff.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Book Services, 1980)
After spending four years with relatives in the South, a fifteen-year-old girl accepts the idea that slaves are property and is horrified to learn when she returns North that her home is a station on the underground railroad.
G1
Keywords: Underground railroad -- Fiction; Young adult fiction